GLS1-mediated glutaminolysis unbridled by MALT1 protease promotes psoriasis pathogenesis - Xia, Xichun (J Clin Invest, 2020)
Psoriasis is a severe disease associated with the disturbance of metabolism and inflammation, but the molecular mechanisms underlying these aspects of psoriasis pathology are poorly understood. Here, we report that glutaminase 1–mediated (GLS1-mediated) glutaminolysis was aberrantly activated in patients with psoriasis and in psoriasis-like mouse models, which promoted Th17 and γδ T17 (IL-17A–producing γδ T) cell differentiation through enhancement of histone H3 acetylation of the Il17a promoter, thereby contributing to the immune imbalance and development of psoriasis. We further demonstrate that mucosa-associated lymphoid tissue lymphoma translocation protein 1 (MALT1) protease was constitutively active in psoriatic CD4(+) and γδ T cells, thereby supporting GLS1 expression by stabilizing c-Jun, which directly binds to the GLS1 promoter region. Blocking the activity of either GLS1 or MALT1 protease resolved Th17 and γδ T17 cell differentiation and epidermal hyperplasia in the psoriasis-like mouse models. Finally, IL-17A enhanced GLS1 expression via the MALT1/cJun pathway in keratinocytes, resulting in hyperproliferation of and chemokine production by keratinocytes. Our findings identify the role of the MALT1/cJun/GLS1/glutaminolysis/H3 acetylation/T17 axis in psoriasis pathogenesis and reveal potential therapeutic targets for this disease.